Oncologic and Functional Outcomes after Partial Nephrectomy Versus Radical Nephrectomy in T1b Renal Cell Carcinoma: A Multicenter, Matched Case-Control Study in Korean Patients - Jang, Hoon Ah (Cancer Res Treat, 2016)
PURPOSE: The study was to compare the oncologic and functional outcomes of partial nephrectomy (PN) and radical nephrectomy (RN) for pathologically proven T1b renal cell carcinoma using pair-matched groups. MATERIALS AND METHODS: We reviewed our prospectively maintained database for RN and PN in T1b renal tumors surgically treated between 1999 and 2011 at five institutions in Korea. Of 611 patients treated with PN or RN for a solitary and NX/N0 M0 renal mass (4-7 cm), 577 (PN, 100; RN, 477) patients with pathologically confirmed pT1b remained for analysis. Study subjects were grouped by PN or RN, then matched by age, sex, comorbidities, body mass index, tumor size and depth, histologic type, and preoperative estimated glomerular filtration rate (eGFR) using propensities score. To evaluate oncologic outcomes, overall survival (OS), cancer-specific survival (CSS), and progression-free survival (PFS) rates were analyzed. The functional outcomes were evaluated by postoperative eGFR. RESULTS: The median follow-up in the RN group was 48.1 and 42.6 months in the PN group. The estimated 10-year CSS rate (PN 85.7% vs. RN 84.4%, p=0.52) and 5- and estimated 10-year PFS rates (PN: 86.4% and 79.2% vs. RN: 86.0% and 66.1%, p=0.66) did not differ significantly between groups. The estimated 10-year OS rate was significantly higher in the PN group (85.7%) compared to the RN group (73.3%) (p=0.003). PN was less likely to induce new-onset chronic kidney disease (CKD) and end-stage CKD compared with RN. CONCLUSION: Our study suggests that patients treated with PN demonstrate a superior OS rate and postoperative renal function with analogous CSS and PFS rates compared with pair-matched patients treated with RN.